Quality of female sterilization counseling in India: A method information index analysis - Manas Ranjan Pradhan; Sourav Mondal; Prasanna Kumar Mudi (Elsevier, 2023)
Problem considered: This study assesses the Method Information Index (MII) for sterilization use and its correlates in India. Methods: National Family Health Survey-5 data (2019-21) was considered for analysis. The sample of women aged 15-49 who adopted sterilization in the last five years preceding the survey (n = 42,480) was included. Binary logistic regression was conducted to examine the adjusted association of socioeconomic and demographic characteristics with MII. Stata (v16.0) was used for the analysis with a 5% significance level. Results: Compared to women who undergone sterilization in a government hospital, the women who had sterilization in a Camp/Mobile clinic/other public facility, Primary health centre/Sub-centre/Urban health post/Government dispensary, and Community Health Centre had respectively, 36% (OR = 0.64, CI = 0.56-0.73), 15% (OR = 0.85, CI = 0.79-0.90) and 14% (OR = 0.86, CI = 0.82-0.91) lower odds of receiving method information. Conclusion: The MII for sterilization was found inadequate, with less than half of the sterilized women being informed about (a) other methods, (b) possible side effects, and (c) side-effects management before adopting the method. Sterilization counseling is positively associated with higher education, exposure to FP messages, social backwardness, urban residence, and services from a government hospital. Regular sensitization of health providers, especially in the lower order health facilities, on the importance of reproductive rights and informed choice seems pertinent. Improved sterilization counseling will also address women's reproductive health and rights and help attain SDG 3.